Professional Issues in Speech-Language Pathology and Audiology, Fifth Edition - Hudson, Melanie W. (Plural Publishing, Incorporated, 2019)
For students in speech-language pathology and audiology this book provides a comprehensive resource as they prepare for their professional careers. It also serves as a timely source of information for both practitioners and faculty, serving as an updated ""state of the professions"" desk reference.